Assessment of Vitamin D and Inflammatory Response Relationship Using Neutrophil to Lymphocyte Ratio, Platelet to Lymphocyte Ratio and Mean Platelet Volume - Elif Umay Altaş; Aliye Tosun (Galenos Yayinevi, 2018)
Objective: Vitamin D is important for calcium and phosphorus metabolism as well as bone homeostasis. Moreover, its receptors were detected in immune system, brain, eyes, pancreas, heart, adipose tissue, thyroid and parathyroid tissues in addition to other tissues and vitamin D deficiency is thought to play a role in immune system response, autoimmune diseases, infectious diseases, some types of cancers, and cardiovascular and metabolic diseases as well. In this study, our main objective is to assess the relationship between 25-hydroxy-D3 [25(OH)D3] deficiency and inflammation; using C-reactive protein (CRP), platelet to lymphocyte rate (PLR), neutrophil to lymphocyte ratio (NLR) and mean platelet volume (MPV) parameters. Materials and Methods: This retrospective-cross-sectional study included 122 patients with diagnosed 25(OH)D3 deficiency and 85 controls. Patients' CRP, NLR, PLR and MPV values were recorded and investigated. Results: There was no significant difference between the patients with 25(OH)D3 deficiency and control group in terms of NLR, PLR and MPV (p>0.05). However, CRP was significantly higher in 25(OH)D3 deficiency patients (p=0.001). No correlation between the values were detected. Conclusion: In our study, CRP values were significantly higher in patients with 25(OH)D3 deficiencies. However, we were unable to find a significant relationship between 25(OH)D3 deficiency and NLR, PLR and MPV values. In order to assess the relationship between inflammation and vitamin D deficiency properly, well-designed prospective randomized controlled studies with wider series are required.